Memproduksi Bahan Semikonduktor Di Dalam Teras Reaktor Nuklir - Mukhlis Akhadi (Sekolah Tinggi Teknik - PLN, 2015)
Behaviour and existing of free electron has attact the attention for the scientist. Researches for studying characteristic of free electron have been carried out in order to utilize such electron in several purposes in the life. Development in solid statesphysics has lead to good understanding of free electron behaviour in state materials. Solid-state physics forms the theoretical basis of materials science. It also has direct applications, for example in the technology of transistors and semiconductors. Throughout the development technology of semiconductor, electron current in semiconductor chips can be utilized for several purposes due to digital codes. Solid-state electronics are those circuits or devices built entirely from solid materials and in which the electrons, or other charge carriers, are confined entirely within the solid material. Recently has been developed a kind of method to produce semiconductor material using nuclear technology. This paper will describe the technology of producing semiconductor material using neutron beam irradiation in a nuclear reactor core. Nuclear technology with neutron beam irradiation can produde very good in quality due to its hight impurityof semiconductor material.